2011
DOI: 10.1002/jsfa.4692
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed intake level on ileal digestibilities of crude protein and amino acids in diets for piglets

Abstract: Because the voluntary feed intake is highly variable in piglets after weaning, comparison of ileal AA digestibilities between and within studies may be confounded by variations in feed intake level. Thus, when designing digestibility studies with piglets, a standardization of feed intake should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
(42 reference statements)
2
7
0
Order By: Relevance
“…It is interesting to note that the AID of most AA decreased for pigs fed a NND diet with increasing FI levels, which is contrary to that for pigs fed a LND diet in the present study. This is in agreement with Goerke et al (2012), who observed that the AID of most AA increased as FI levels increased from 4.5 to 6% of BW for piglets fed a diet at 23% CP. A linear decrease in the AID of most AA in SBM was reported when dietary CP ranged from 165 to 255 g/kg (from adequate to excess) in the experiment of Li et al (1993).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…It is interesting to note that the AID of most AA decreased for pigs fed a NND diet with increasing FI levels, which is contrary to that for pigs fed a LND diet in the present study. This is in agreement with Goerke et al (2012), who observed that the AID of most AA increased as FI levels increased from 4.5 to 6% of BW for piglets fed a diet at 23% CP. A linear decrease in the AID of most AA in SBM was reported when dietary CP ranged from 165 to 255 g/kg (from adequate to excess) in the experiment of Li et al (1993).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the results of Peers et al (1977) and Smits et al (1994), who reported that the digestibility of DM and GE in barley, legume seeds, maize byproduct, and wheat byproduct was not affect by FI levels. Moreover, Moter and Stein (2004) and Goerke et al (2012) demonstrated that the digestibility of DM and GE were not influenced by FI levels for pigs fed cornstarch-based diets. Morel et al (2006) suggested that the effect of FI on nutrient and GE digestibility depends on the quality of the feed.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations